Estudo do método de inversão tomográfica 2D baseada nos atributos cinemáticos da onda NIP e construção de interface gráfica para o processo de picking - OLIVEIRA, Iran Gadelha de (Universidade Federal do Pará, 2014)
In this work, a new tomographic reflection inversion method is studied, with the objective of determining smooth and isotropic velocity models for real and synthetic seismic data. The velocity model is obtained by the program NIPTOMO, which is an implementation of a tomographic inversion method of the kinematic attributes of the hypothetical waves NIP (normal incidence point). The input data for the tomographic inversion, e. g., traveltime tables and NIP attributes (wavefront curvature radius and emergence angle) are obtained through a set of picked points on a simulated zero-offset (ZO) section, previously obtained by the common-reflection surface (CRS) method. The choice of picked points in a ZO section is normally made using automatic picking programs that identify locally coherent events in a seismic section, based in user-defined parameters. The picking process is one of the most critical steps in this new method, since the choice of non primary reflection events, such as diffractions and multiples, may lead to errors in the velocity model obtained by the tomographic inversion. This work has as main objective develop an interative picking program to give to the user the control of the choice of primary reflection points that are used as input for the tomographic inversion. The present picking program was tested on the synthetic Marmousi dataset and on a real data from the Tacutu Basin, Brazil (seismic line 50-RL-90). The results obtained show that the interative picking process for the choice of primary reflection events points favors the determination of a precise velocity model.